Kesultanan Banjar dan Kontribusinya Terhadap Sistem Hukum Islam di Nusantara - Wigati, Nani (Al Hikmah, 2025)
The Sultanate of Banjar has significantly contributed to the Islamic legal system in the Nusantara since the 16th century. This research aims to explore the role of the Sultanate of Banjar in the dissemination and establishment of an inclusive and just Islamic legal structure. The research employs a qualitative method with historical and sociological approaches, including the analysis of historical documents, ancient manuscripts, and observations of contemporary legal practices. The findings indicate that the Sultanate of Banjar successfully integrated customary law with Islamic law, creating a harmonious legal system that influences the present day. The novelty of this research lies in its holistic and multidisciplinary analysis, providing a deep understanding of the Sultanate of Banjar's contribution to the development of Islamic law in the Nusantara. This research suggests further studies to explore the contributions of other sultanates in the Nusantara in similar contexts.